2011
DOI: 10.1111/j.1349-7006.2011.02034.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of breast cancers detected by ultrasound screening in women with negative mammograms

Abstract: Screening ultrasound (US) can increase the detection of breast cancer. However, little is known about the clinicopathologic characteristics of breast cancers detected by screening US. A search of the database for patients with breast cancer yielded a dataset in 6837 women who underwent breast surgery at Seoul National University Hospital (Korea). Of 6837 women, 1047 were asymptomatic and had a non-palpable cancer. Two hundred fifty-four women with 256 cancers detected by US (US-detected cancer) and 793 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Currently the treatment strategy of NPBC is made according to palpable cancers of similar stage, subtype and grade [30]. Bae MS et al reported comparison study between 807 MG-detected NPBC vs 256 US-detected NPBC [31]. However, the 807 (MG+/US not done) NPBC would include some MG+/US- NPBC and majority of MG+/US+ NPBC patients, while the 256 US-detected NPBC patients were all MG-/US+.…”
Section: Discussionmentioning
confidence: 99%
“…Currently the treatment strategy of NPBC is made according to palpable cancers of similar stage, subtype and grade [30]. Bae MS et al reported comparison study between 807 MG-detected NPBC vs 256 US-detected NPBC [31]. However, the 807 (MG+/US not done) NPBC would include some MG+/US- NPBC and majority of MG+/US+ NPBC patients, while the 256 US-detected NPBC patients were all MG-/US+.…”
Section: Discussionmentioning
confidence: 99%
“…Since the CAD could not be perfect (100 % sensitivity and 100 % specificity), the cut-off point with sensitivity of 95 % (20/21, one malignant case misclassified) can be chosen for the classification in a clinical setting. Recognizing the carcinomas among the BI- RADS category 3 lesions is important since circumscribed malignant lesions are often high-grade tumors [26][27][28]. The proposed CAD system can correctly upgrade most of malignant masses misclassified as BI-RADS category 3 on US by radiologists while downgrade majority of benign lesions classified as BI-RADS category 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, subjects who underwent ultrasonography for breast cancer screening during their lifetime made up nearly half of the population in Korea. There are reports that breast density appears to be greater in Asian women than in Western women (del Carmen et al, 2007), and ultrasound has been proposed as a supplemental screening test in women with dense breast tissues (Corsetti et al, 2006;Bae et al, 2011).…”
Section: Discussionmentioning
confidence: 99%